Drilling for Gold - JOHN WARRILLOW (John Wiley & Sons, Inc., 2002)
The small business market is the most important on earth. The majority of our family and friends depend on small businesses for their paychecks. Most of America’s economic output is generated by small business. The world’s great inventions—from the light bulb to the automobile—are gifts from the mind of an entrepreneur. More college graduates would rather start a business than be the president of the United States.1